PENETAPAN KENAIKAN UPAH MINIMUM PROVINSI (UMP) DKI JAKARTA: STUDI KASUS KEPUTUSAN GUBERNUR DKI JAKARTA ANIES BASWEDAN NOMOR: 1517 TAHUN 2021 - Umar Ali Zain (2023)
The purpose of this study is to discuss the Determination of the DKI Jakarta Provincial Minimum Wage Increase: A Case Study of DKI Jakarta Governor Anies Baswedan's Decree Number 1517 of 2021.The method used is descriptive qualitative. The main theory in this study is the multicurrent theory from John W Kingdon. This theory is used as an analytical tool in the policy formulation of DKI Jakarta Governor Decree Number 1517 of 2021 for the determination of the DKI Jakarta Provincial Minimum Wage of 2022.The results of this study are the role of actors such as experts, academics as supporting actors and the role of DKI Jakarta Provincial Government and trade unions as the main actors pushing for policy changes regarding DKI Jakarta UMP in 2022. The process of identifying problems related to DKI Jakarta UMP is part of problem flow, the Provincial Government of DKI Jakarta tried to identify problems regarding the DKI Jakarta UMP which turned out to be an increase that was below what was said to be feasible. Pemprov identified that wages for the last six years in DKI Jakarta averaged 8.6%, then inflation in DKI Jakarta was 1.14%. The problem cannot be separated from the workers' unions by looking at the policy to increase the DKI Jakarta UMP which is very under the word feasible. The selection process for increasing the DKI Jakarta UMP to 5.1% defeated proposals from other actors. This process is part of the policy stream, the 5.1% increase indicates that the power relations exercised by DKI Jakarta Governor Anies Baswedan over other actors are unable to intervene in decisions made by the governor. The increase in the DKI Jakarta UMP is inseparable from political currents that put pressure on the Governor of DKI Jakarta Anies Baswedan which was carried out by trade unions.